Improving positive emotions and job dedication to foster safety participation - Margheritti, S.; Silva, S.A.; Negrini,A.; Miglioretti,M. (“ 1ª Conferência de Saúde Societal, 2022)
Nowadays, promoting a safer work environment is one of the organizations most significant challenges. In fact, despite the several interventions made, accident and injury rates continue to be high. For a long time, research in this area has focused only on safety prevention, investigating the negative factors leading workers to make mistakes (e.g., lack of attention, loss of motivation, or 47 higher job demands) and incurring accidents and injuries. Thus, research has understudied the role of positive resources in promoting safety behaviors without investigating peoples behaviors that help the work environment be healthier. These types of behaviors, called safety participation, are not formally prescribed by job descriptions but are favorable and voluntary. Previous research showed it is associated with a healthier work environment (Neal & Griffin, 2006). Starting from the Job Demands-Resources Model (JD-R) framework (Bakker & Demerouti, 2007, 2017), the objective of the present study is to investigate the role of some job resources (i.e., autonomy) and personal resources (i.e., hope) in promoting safety participation. Specifically, this study focused on the role of two mechanisms underlying this relationship: positive emotions and job dedication (as a part of work engagement). In addition, we investigated the role of job demands (i.e., workload) in moderating the relationship between the previous variables. A cross-sectional study was conducted involving 225 people working from a multinational corporation allocated in different countries (Portugal, Spain, Italy, Germany, and Greece). Data were analyzed using moderated serial mediation analysis with SPSS software. Results showed that autonomy and hope are associated with safety participation through positive emotions and job dedication. Positive emotions and job dedication are indeed serial mediators in the previous relationship. At the same time, workload moderates the relationship between job dedication and safety participation. Thus, when the workload is higher, workers job dedication is not sufficient anymore to promote safety participation. In addition, workload moderates overall the serial mediation path, indicating that when the workload is higher, the positive connection between resources and safety participation disappears. These results showed that when workers feel resourceful, they also feel positive emotions and are more dedicated at work. Experiencing positive emotions and being engaged at work made workers implement positive safety behaviors more frequently, such as safety participation. At the same time, having too many job demands to deal with bring resourceful workers not to behave safety participation. Thus, their resources could be focused on coping with job demands and can t be used to achieve safe, voluntary behaviors. Our finding underlined that positive emotions and job dedication are essential in the safety arena, expanding the previous research on this topic. Safety-critical enterprises, consulting firms, and safety managers should realize this and develop good employee attitudes to improve employee safety performance. In addition, organizations should reflect on their job demand levels and help workers deal with them. Only in this way would positive resources positively promote a healthier work environment.